2003
DOI: 10.1536/jhj.44.369
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Low-Molecular Weight Heparins for the Prevention of Thromboembolic Events after Cardioversion of Atrial Fibrillation

Abstract: SUMMARYTransesophageal echocardiography (TEE) guided early cardioversion (CV) in conjunction with short-term anticoagulation has been shown to be safe, and an alternative to prolonged conventional anticoagulation therapy. Recently, low molecular weight heparins (LMWHs) have been used successfully as an alternative to standard heparin therapy obviating the need for hospitalization and APTT monitoring. The aim of this study was to determine the feasibility and safety of TEE guided early cardioversion in conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Approximately half of the patients included in each group underwent electrical CV or medical CV; no thromboembolic events occurred during the 4 weeks following CV. Even though TTE was performed in all patients, and a control group with standard heparin was included, no adjustment of LMWH for patient's weight was performed, and no information about treatment duration before and after CV was provided [22].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the patients included in each group underwent electrical CV or medical CV; no thromboembolic events occurred during the 4 weeks following CV. Even though TTE was performed in all patients, and a control group with standard heparin was included, no adjustment of LMWH for patient's weight was performed, and no information about treatment duration before and after CV was provided [22].…”
Section: Discussionmentioning
confidence: 99%
“…We identified 220 articles representing 117 studies relevant to KQ 3 (Appendix Table F-3). [23][24][25][26]112,113,115,124,127,134,141,169,177,179,187,188,197, A total of 22 RCTs [23][24][25][26]113,115,215,219,232,233,250,276,288,289,315,320,321,339,354,358,366,371 and 95 observational studies 112,127,141,177,207,208,214,218,220,221,[226][227][228][229][230]238,239,<...>…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…[23][24][25][26]113,232,233,288,375 Two studies were unclear or did not report a geographical location. 115,366 Seventy-five studies were considered of good quality or had a low risk of bias rating, 23-26,112,113,115,127,173,177,207,208,214,218,219,228-230,232,233,250,255,258,259,267-269,275,276,287,288,293,294,297,299,300,303-305,310,311,320-322,327,329,330,339,346,347,362,365,366,370,373,376,379-382,387,388,391-393,395,396,398,400-402,405-409 16 were considered fair quality or had a moderate risk of bias rating, 215,289,315,350,354,358,371,375,[383][384][385][386]389,394,397,403 and 26 were of poor quality or had a high risk of bias rating. 141,220,221,226,227,238,239,253,257,262,264,266,273,292,295,298,302,[307][308]…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Yigit et al studied 172 patients; all of whom received warfarin after cardioversion, in addition to either dalteparin or unfractionated heparin started prior to cardioversion. The authors concluded that TEE-guided cardioversion with dalteparin (n=90) was as safe as TEEguided cardioversion with unfractionated heparin (n=82) for the prevention of thromboembolic events after cardioversion [38]. Bechtold et al investigated the effects of 2Â100 antiXa IU/kg (with a maximum dose of 2Â10,000 anti-Xa IU) of dalteparin for a median of 11 days in 125 AF patients, concluding that simple, well-tolerated, and effective anticoagulation is possible with dalteparin [39].…”
Section: Choice Of Heparin Accompanying Cardioversionmentioning
confidence: 99%